2015
DOI: 10.3233/ch-131764
|View full text |Cite
|
Sign up to set email alerts
|

Skin microcirculation in healthy term newborn infants – assessment of morphology, perfusion and oxygenation

Abstract: Day 1-3 (mean (SD)): Microvascular density (CAVM; number of microvessels crossing a grid of lines/mm line, c/mm): Chest: 11.3 (1.5), 11.0 (1.7), 10.7 (1.6). Hand: 13.2 (2.0), 13.2 (1.9), 12.4 (1.6). Capillary density was significantly higher in the hand than in the chest each day (p < 0.001). Perfusion (LDPM; arbitrary units): Chest: 109.1 (26.0), 101.4 (24.6), 100.8 (25.3). Hand: 58.9 (17.5), 54.3 (15.8), 46.9 (14.8). Perfusion was significantly higher in the chest than in the hand each day (p < 0.01). Microv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 31 publications
5
20
0
Order By: Relevance
“…In our previous study, we suggested that the increased FCD during cooling compared to healthy term neonates was probably a compensation for reduced oxygen diffusion with lower temperatures [11,17]. In the present study, FCD became significantly lower after rewarming in the high-CRP group compared to infants with low CRP.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In our previous study, we suggested that the increased FCD during cooling compared to healthy term neonates was probably a compensation for reduced oxygen diffusion with lower temperatures [11,17]. In the present study, FCD became significantly lower after rewarming in the high-CRP group compared to infants with low CRP.…”
Section: Discussionsupporting
confidence: 65%
“…After rewarming, the high-CRP group had significantly more flow in category 5 compared to the infants with low CRP (p < 0.01). In the low-CRP group, 95% of the capillaries had similar velocities as found in healthy normotherm neonates (category 3 and 4) [17] following rewarming compared to only 71% in the high-CRP group.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…With the CAVM technique, capillary morphology and physiology can be visualized and described according to size, shape, density, and blood flow velocity. 7,8,[14][15][16][17] Capillaries were defined as microvessels with a diameter <15 μm. Not all capillaries in a tissue are perfused at a given per millimeter line (c/mm).…”
Section: Cavmmentioning
confidence: 99%
“…These techniques have been applied in studies of patients with acute heart failure and in healthy and sick newborns. [7][8][9] The measuring depth of the DRS and CAVM methods has been estimated in theoretical models, 10,11 but it remains to be shown that the two techniques in humans assess papillary nutritive perfusion only.…”
mentioning
confidence: 99%